“Dinámica poblacional de insectos en el cultivo de stevia (stevia rebaudiana bertoni) durante la etapa fenológicade brotacion, en el alto mayo” - Sánchez Ojanasta, Martín (2015)
This research was conducted in the fields of production company STEVIAONE, located in the district of Pardo Miguel, province of Rioja, Department of San Martín, the same that was developed during the period between the months of late the month of August 2013 to January, 2014. The methodology used was weekly assessments of pest and beneficia! insects to locate their taxonomic position, held with the support of SENASA. The research area was heavily organic soil with acid pH, high organic matter. With average temperature of 21.6 º C, relative humidity 82. 7% d and 234.5 mm of rainfall in the months of study. The analysis was by descriptive statistics and not used any statistical design. The results obtained during the experiment focused on two variables, presence of insect pests and beneficia! insects present. During the phonological stages of flowering sprouting stevia the population of insects captured by plant species belong to the Systena sp, Coleoptera, family Chrysomelidae, with 1069 individuals in the growth stage 1and1078 individuals in the growth stage 11. Other insect pest populations are representative species of Trialeurodes sp and Phenacoccus sotaní, with 266 and 476 individuals in total recorded during the investigation, the former being more stable populations in the growth stages 1 and 11 and flowering 78, 91 and 70 individuals respectively. During the experiment we have identified 10 species of insect pests (Trialeurodes sp, Tetrogonia sp, Proba visttitus,Phenacoccus so/ani, Systena sp, Diabrotica sp, Gryllus sp, Spodoptera sp and Pseudop/usia sp) in total, 6 families (Aleyrodidae, Cicadellidae, Pseudococcidae, Chrysomelidae, Gryllidae and Noctuidae) and 4 orders (Hemiptera, Coleoptera, Orthoptera and Lepidoptera) Was also identified thou species of beneficia! insects (Cycloneda sp, Hippodania sp), 2 families (Coccinellidae and Pentatomidae) and two rows (Coleoptera and Hemiptera). Keyswords: Stevia, steviosido, pest, beneficia!, phonologycal, growth, flowering.